Immune Inspired Approach for Securing Wireless Ad hoc Networks - Yasir Abdelgadir , Mohamed; Azween, Abdullah (2009)

(untitled)
New computational techniques are being developed based on the immune system concepts, seeking to solve several engineering problems. Moreover, mobile ad hoc networks (MANETs) have no clear line of defense and no fixed infrastructure; therefore, the known security techniques used for cabled networks might not work perfectly. A security approach based on immune inspired properties and features is presented. Mobile agent system has been used so as to map different immune components that collaborate to defend the human body against different kinds of diseases. Distributed detection, first response, second response, self recovery, adaptability, and danger theory representation are the hallmarks of the proposed security approach which places emphasis on infrastructure less and high nodes mobility capabilities.